An Odd Oxygen Framework for Wintertime Ammonium Nitrate Aerosol Pollution in Urban Areas: NOx and VOC Control as Mitigation Strategies. Issue 9 (8th May 2019) - Womack, C. C.; McDuffie, E. E.; Edwards, P. M.; Bares, R.; de Gouw, J. A.; Docherty, K. S.; Dubé, W. P.; Fibiger, D. L.; Franchin, A.; Gilman, J. B.; Goldberger, L.; Lee, B. H.; et al.
Abstract: Wintertime ammonium nitrate aerosol pollution is a severe air quality issue affecting both developed and rapidly urbanizing regions from Europe to East Asia. In the United States, it is acute in western basins subject to inversions that confine pollutants near the surface. Measurements and modeling of a wintertime pollution episode in Salt Lake Valley, Utah, demonstrate that ammonium nitrate is closely related to photochemical ozone through a common parameter, total odd oxygen, Ox, total . We show that the traditional nitrogen oxide and volatile organic compound (NOx‐VOC) framework for evaluating ozone mitigation strategies also applies to ammonium nitrate. Despite being nitrate‐limited, ammonium nitrate aerosol pollution in Salt Lake Valley is responsive to VOCs control and, counterintuitively, not initially responsive to NOx control. We demonstrate simultaneous nitrate limitation and NOx saturation and suggest this phenomenon may be general. This finding may identify an unrecognized control strategy to address a global public health issue in regions with severe winter aerosol pollution. Plain Language Summary: Particulate matter (PM) is dangerous to human health and impacts visibility and climate. In the United States, Europe, and Asia, PM is severe in urban areas in the winter when ammonium nitrate, NH4 NO3, comprises an appreciable fraction of the total PM mass. A key control strategy is to reduce emissions of the limiting reagent. Using measurements from a recent field campaign in the Salt Lake Valley, Utah, which experiences high PM levels in winter, we demonstrate that emission control strategies can be evaluated using the same framework commonly used to control ozone, another common pollutant that occurs at high levels in urban areas in the summer. We show that initial control of the NOx precursor is ineffective at reducing NH4 NO3 aerosol in the Salt Lake Valley, while initial control of volatile organic compounds, which are not a direct precursor for either nitrate or ammonium, is effective due to their influence on oxidation cycles. This finding differs from many mitigation strategies in the western United States and may also be relevant to other regions in Europe and Asia which experience high wintertime PM. Key Points: Wintertime ammonium nitrate aerosol pollution is closely tied to photochemical ozone production through a common parameter, Ox, total Box modeling reveals ammonium nitrate formation in the Salt Lake Valley is nitrate‐limited but NOx ‐saturated Mitigation strategies that focus on NOx control in some wintertime‐polluted layers may initially increase ammonium nitrate